Satisfaction and attitude of bipolar patients regarding electroconvulsive therapy: modified or unmodified. (17th February 2020) - Atay, Özge Canbek; Bag, Sevda; Usta, Haluk; Çetinkaya, Esin; Yanik, Medaim
Abstract: Objective: Ministry of Health of Turkey issued a legislation to use only modified electroconvulsive therapy (ECT) in 2005, and this study aimed to assess satisfaction and attitude of bipolar patients regarding modified and unmodified electroconvulsive therapy. Methods: A total of 100 patients (50 treated with modified electroconvulsive therapy (M-ECT) and 50 treated with unmodified ECT (UM-ECT) with a diagnosis of Bipolar Disorder (depressive or manic episode) were invited to participate in this study. Patients with euthymic mood were included. Satisfaction and attitude towards ECT were evaluated with a structured attitude questionnaire, and M-ECT and UM-ECT patients, and their subgroups (depressive vs. manic) were compared. Results: No significant differences were found between M-ECT and UM-ECT groups regarding age, sex, marital status and occupation. The majority of all patients (78%) were satisfied from treatment with ECT and with the outcome (88%), without significant differences between modified and unmodified groups. Forgetfulness (70%) and headaches (57%) occurred in all groups, with the only significant difference in forgetfulness being reported by more manic patients treated with UM-ECT. Depressive and manic patients treated with UM-ECT reported concerns of brain damage and physical harm significantly more frequently. While 86% of patients treated with M-ECT consented to a future treatment, this was significantly less in patients treated with UM-ECT (50%). Conclusions: Bipolar patients report a high degree of satisfaction treated either with modified or unmodified ECT but there was a significant difference in perception of adverse effects and willingness for receiving ECT in future.